The Role of The Principal in Creating A Positive Work Environment for Teachers at SDN Palasah 1, Majalengka Regency - Helsa Liski; Siti Khumayah (Journal of Comprehensive Science, 2026)
A positive work environment is an essential factor in improving teacher professionalism and learning quality in elementary schools. However, differences in teacher readiness, adaptability, and professional commitment remain challenges for school leaders in creating a supportive organizational climate. This study aims to examine the role of the principal in fostering a positive work environment for teachers at SDN Palasah 1, Majalengka Regency, based on Hersey and Blanchard’s situational leadership model, as well as to identify leadership challenges and the efforts implemented to address them. This research employed a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews with the principal, teachers, and supporting informants selected through purposive sampling. Data validity was ensured through source, methodological, and theoretical triangulation. The results indicate that the principal applied flexible leadership strategies through directing, guiding, participating, and delegating styles according to teachers’ levels of professional readiness. Academic supervision, open communication, collaborative decision-making, and peer mentoring programs contributed to strengthening teacher motivation and professional development. The main challenges included differences in teacher competencies, technological adaptation, and varying responses to organizational change. The principal addressed these challenges through continuous support, individualized guidance, and collaborative learning practices. This study concludes that adaptive instructional leadership plays a significant role in establishing a harmonious, productive, and sustainable teacher work environment.